Comparison of Methods Used in European Countries to Assess Buildings' Condition - Vilhena, António (2012)
This paper presents a comparative analysis of methods used in European countries to assess buildings’ condition. The following methods were compared: a Portuguese method to assess buildings condition, an English housing health and safety rating system, a French method to assess buildings that may be declared inhabitable, a Dutch standard about buildings condition assessment and the assessment methods developed within the European projects EPIQR & TOBUS. The comparative analysis included three tasks. First, each of the methods was described separately. Then, the main features of the methods were compared. Finally, some guidelines to improve the Portuguese method were drawn. The main differences of the methods are the objectives and scope of the assessment, the disaggregation level of the global assessment, the calculation formula used to aggregate partial assessments, the type final results obtained and the tools developed for their implementation. The main similarities are that the assessment is carried out mainly by visual inspection, the condition of the building is assessed by a systematic analysis of the entire building divided into functional elements, the severity of defects is the assessment criterion used, weighting coefficients are used to determine the importance of each partial assessment in the final result and surveyors need specific training. The recommendations about the Portuguese method are to maintain the present assessment model, to carry out the training courses of surveyors, to create a complementary tool for the diagnosis of the causes of defects and to develop a computer program to support surveyors during inspections.